Testing the thermal limits of Eccritotarsus catarinensis: a case of thermal plasticity. Issue 6 (3rd June 2019) - Porter, Jordan D.; Owen, Candice A.; Compton, Stephen G.; Coetzee, Julie A.
ABSTRACT: Water hyacinth is considered the most damaging aquatic weed in South Africa. The success of biocontrol initiatives against the weed varies nation-wide, but control remains generally unattainable in higher altitude, temperate regions. Eccritotarsus catarinensis (Hemiptera: Miridae) is a biocontrol agent of water hyacinth that was first released in South Africa in 1996. By 2011, it was established at over 30 sites across the country. These include the Kubusi River, a site with a temperate climate where agent establishment and persistence was unexpected. This study compared the critical thermal limits of the Kubusi River insect population with a laboratory-reared culture to determine whether any physiological plasticity was evident that could account for its unexpected establishment. There were no significant differences in critical thermal maxima (CTmax ) or minima (CTmin ) between sexes, while the effect of rate of temperature change on the thermal parameters in the experiments had a significant impact in some trials. Both CTmax and CTmin differed significantly between the two populations, with the field individuals tolerating significantly lower temperatures (CTmin : −0.3°C ± 0.063 [SE], CTmax : 42.8°C ± 0.155 [SE]) than those maintained in the laboratory (CTmin : 1.1°C ± 0.054 [SE], CTmax : 44.9°C ± 0.196 [SE]). Acclimation of each population to the environmental conditions typical of the other for a five-day period illustrated that short-term acclimation accounted for some, but not all of the variation between their lower thermal limits. This study provides evidence for the first cold-adapted strain of E. catarinensis in the field, with potential value for introduction into other colder regions where water hyacinth control is currently unattainable.